2020
DOI: 10.2166/ws.2020.321
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive water testing analyses for improved water management: coliforms, coliphage and cholesterol

Abstract: The use of feacal coliforms as indicators is the traditional approach of testing water quality. Unfortunately, for a comprehensive water quality analysis, there is an increasing body of evidence that demonstrates coliforms as insufficient indicators for water quality assessment. Therefore, during the last two decades, alternative water testing approaches such as the use of coliphage as well as cholesterol detection have gained popularity. In the present study, we evaluated and compared the reliability of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, as will be further demonstrated, the proposed method was applied in water samples practically undiluted, which denotes the absence of interference from water samples. One should note still that bearing in mind the previous studies carried out for the CHO determination in water samples and sediments as an indicator of fecal pollution using chromatographic techniques [7,8,[41][42][43], the detectability herein obtained is enough for this purpose.…”
Section: Interference Studymentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, as will be further demonstrated, the proposed method was applied in water samples practically undiluted, which denotes the absence of interference from water samples. One should note still that bearing in mind the previous studies carried out for the CHO determination in water samples and sediments as an indicator of fecal pollution using chromatographic techniques [7,8,[41][42][43], the detectability herein obtained is enough for this purpose.…”
Section: Interference Studymentioning
confidence: 78%
“…Coprostanol has been used as a biomarker of pollution by domestic sewage as such hormone is produced in the digestive tracts of humans and higher vertebrates from the microbial reduction of cholesterol (CHO) [6]. Moreover, studies have reported that CHO, one of the major sterols in aquatic environments, has a high positive correlation with coprostanol and its higher concentration in water samples must likely be associated with domestic effluent inputs and, thus has also been considered a sterol biomarker for animal fecal pollution [7, 8].…”
Section: Introductionmentioning
confidence: 99%